A PERENCANAAN TALUD PENGAMAN TEBING SUNGAI DI YAYASAN AL-MADINAH DAERAH WARA RT.008/RW.019 JLN. WARASIA, BATU MERAH, KEC. SIRIMAU, KOTA AMBON : Dinding Penahan Tanah Tipe Gabion - Nadila Faradila Soo; Steanly R.R Pattiselanno (JURNAL SIMETRIK, 2026)
Riprap is a retaining wall that serves to maintain the stability of the soil and slopes. A gabion-type retaining wall is one method of river bank protection that uses a box-shaped galvanized steel wire mesh structure (gabion), which is filled with split stone. The active river located in the Wara area,Batu Merah Village, Ambon City, is the target of this study. Based on field data obtained by the author,one of which,is a statement from the head of the Al-Madinah Foundation, it is said that in the last 13 years there have been 2 floods and soil erosion by river (erosion) and the formation of water bends that slowly enter the foundation's riverbank area, requiring gabion planning as a solution to hold water runoff and soil carried by river water currents. The data used is soil data to obtain the friction angle,soil cohesion and soil bulk density. For the gabion wire mesh, thick galvanized mild steel wire with a tensile strength of 41-53 kgf/mm2 was used. The specific gravity of split stone used in this design was 1,500 kg/m³ for the gabion filler. These values refer to SNI 03-2834-2000 standards to produce adequate gabion dimensions with a structure that meets the safety factors for soil bearing capacity, overturning, and shear. The calculated overturning force was 72≥1.5 and the shear force was 36≥1.5, thus categorizing the gabion construction as safe. with dimensions of 2 x 1 x 0.5, 1 partition, and a capacity of 1 m³,with a total cost of Rp. 1,182,693,36.- Keywords: Retaining Wall; Gabion; River Bank